Efektivitas Komunikasi Kesehatan Upaya Peningkatan Pengetahuan Ibu Tentang Stunting Di Desa Gili Timur - Pratiwi, Gabriel Beti; Kurniasari, Netty Dyah (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
This study was conducted to observe the effectiveness of health communication efforts to increase mothers' knowledge about stunting in Gili Timur Village. The approach used in this study was qualitative in data collection techniques with interviews. The results of the study showed that health communication that had been implemented through socialization of stunting prevention, education on processing food properly, demonstrations of stunting prevention using social media and mass media had succeeded in increasing mothers' knowledge about stunting starting from the causes, impacts of stunting, and how to prevent stunting. So that this study can be seen that health communication has an important role in changing the behavior of mothers to children in preventing stunting. In an effort to increase the effectiveness of health communication, it is recommended to use material discussions according to needs so that they are easily understood by mothers. Therefore, health communication requires improvement through an approach with a primary focus on the needs or requirements of mothers in certain groups.